2019
DOI: 10.1002/glia.23687
|View full text |Cite
|
Sign up to set email alerts
|

Questions and (some) answers on reactive astrocytes

Abstract: Astrocytes are key cellular partners for neurons in the central nervous system. Astrocytes react to virtually all types of pathological alterations in brain homeostasis by significant morphological and molecular changes. This response was classically viewed as stereotypical and is called astrogliosis or astrocyte reactivity. It was long considered as a nonspecific, secondary reaction to pathological conditions, offering no clues on disease‐causing mechanisms and with little therapeutic value. However, many stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
180
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(213 citation statements)
references
References 225 publications
8
180
0
5
Order By: Relevance
“…When compared to SAL mice, Glu levels were increased at the dCA1 in METH mice (p = 0.0187, n = 11 Figure 1 METH withdrawal weakened astrocytic capacity of Glu uptake at dCA1 tripartite synapses, and EA treatments normalizing the function of astrocyte Complement component 3 (C3), S100A10 and glial fibrillary acidic protein (GFAP) were used as markers for the A1-like, A2-like and all astrocytes respectively here. As previously reported, reactive astrocyte shows thicker cellular processes and larger body compared to the resting ones 20 . When compared to SAL mice, METH withdrawal significantly increased the proportion of C3-positive A1like astrocytes (p = 0.0016, n = 12) and reactive astrocytes (p = 0.0007, n = 12), but failed to alter the total number of GFAP-positive astrocyte (p = 0.0961, n = 12, Figure 2 A1), the proportion of 6 S100A10-positive A2-like astrocytes (p = 0.1921, n = 12, Supplemental Figure 3 A1) and the protein levels of S100A10 (p = 0.9050, n = 6, Supplemental Figure 3 B1) at dCA1.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…When compared to SAL mice, Glu levels were increased at the dCA1 in METH mice (p = 0.0187, n = 11 Figure 1 METH withdrawal weakened astrocytic capacity of Glu uptake at dCA1 tripartite synapses, and EA treatments normalizing the function of astrocyte Complement component 3 (C3), S100A10 and glial fibrillary acidic protein (GFAP) were used as markers for the A1-like, A2-like and all astrocytes respectively here. As previously reported, reactive astrocyte shows thicker cellular processes and larger body compared to the resting ones 20 . When compared to SAL mice, METH withdrawal significantly increased the proportion of C3-positive A1like astrocytes (p = 0.0016, n = 12) and reactive astrocytes (p = 0.0007, n = 12), but failed to alter the total number of GFAP-positive astrocyte (p = 0.0961, n = 12, Figure 2 A1), the proportion of 6 S100A10-positive A2-like astrocytes (p = 0.1921, n = 12, Supplemental Figure 3 A1) and the protein levels of S100A10 (p = 0.9050, n = 6, Supplemental Figure 3 B1) at dCA1.…”
supporting
confidence: 83%
“…Cells were then resuspended in 10 mL of medium and cultured in a well-prepacked flask for 1 d. Finally, the flask was shaken at 200 rpm for 2h at 37 ° C. After two purification processes, purified astrocyte cultures were obtained, which were constituted by more than 95% of GFAP-positive cells. A1 reactive astrocytes were generated in vitro by growing purified astrocytes for 6 days and then treated with Il-1α (3 ng/mL, 20 STEMCELL, 78115), TNFα (30 ng/mL, Cell Signaling Technology, 8902SF), and C1q (400 ng/mL, abcam, ab96363) for 24 h 12 .…”
Section: Primary Astrocyte Culture and Treatmentmentioning
confidence: 99%
“…After this point, the SCI lesion begins to stabilize, and a long chronic phase of regeneration begins. It is worth mentioning that the STAT3 pathway, a master regulator of astrocyte activation and glial scar formation, also controls glial scar maturation (Ceyzériat et al, 2016;Escartin et al, 2019). In STAT3-KO mice, the elongated processes of scar-forming astrocytes remain perpendicular to the lesion core and do not become parallel to form a dense astrocytic scar border after SCI (Wanner et al, 2013).…”
Section: Glial Scar Maturation Within Weeksmentioning
confidence: 99%
“…However, the glial scar is not only anti-inflammatory. After SCI, reactive astrocytes, microglia and peripheral immune cells release proinflammatory cytokines and interact with each other, which contributes to the inflammation in the acute and subacute stage (Escartin et al, 2019). Reactive astrocytes also have negative feedback regulation for inflammation after SCI (Haan et al, 2015;Zhang et al, 2019).…”
Section: Beneficial Rolesmentioning
confidence: 99%
“…Already in these early studies two main facets of gliotic response have been recognized: these being astroglial hypertrophy and astroglial proliferation. Astroglial proliferations in the context of astrogliotic response have been somewhat neglected and was questioned recently, which probably reflects a wide diversity of glial reactive remodelling in different pathologies—not always the proliferative component comes fore. Nonetheless a subpopulation of reactive astrocytes with prominent proliferative capabilities has been found in the vicinity of focal brain lesions, while recent studies of Milos Pekny and his colleagues have identified the sub‐population of astrocytes expressing intermediate filament protein nestin, which confers proliferative capacity and seem to play a role in the hippocampal neurogenesis with the absence of nestin leading to enhanced reversal place learning and memory extinction …”
mentioning
confidence: 99%